(untitled) (Impetus, 2021)
Why study neighborhood clubs? What kinds of issues or problems can be observed in these institutions where sports, games, gymnastic activities are practiced, among other practices? We argue that neighborhood clubs are, on the one hand, places where it is possible to capture and study certain practices of construction of identities -individual and collective-, processes of subjectivation and subjection of individuals, places where in the apparent aseptic practice of teaching From sports or games, strong processes of transmission of values ​​and valorizations are produced, places where senses that are not neutral are aturalized and hide their ideological belonging, where children and young people are accustomed to certain behaviors, obediences, subjection to norms, and they experience certain exercises of power, where social and / or gender inequalities are also reproduced and consolidated.